Compositional Dependence of Magnetocrystalline Anisotropy in Fe-, Co-, and Cu-Alloyed Ni-Mn-Ga - Michal Rameš; Vít Kopecký; Oleg Heczko (Metals, 2022)
The key for the existence of magnetic induced reorientation is strong magnetocrystalline anisotropy, i.e., the coupling between ferroelastic and ferromagnetic ordering. To increase the transformation temperatures and thus functionality, various elemental alloying in Ni-Mn-Ga is tried. We analyzed more than twenty polycrystalline alloys alloyed by small amount (up to 5atom%) of transitional metals Co, Fe, Ni, and Cu for the value of magnetic anisotropy in search of general trends with alloying. In agreement with previous reports, we found that maximum anisotropy occurs at stoichiometric Ni2MnGa and any alloying decreases its value. The strongest decrease of the anisotropy is observed in the case where the alloyed elements substitute Ga.